2016
DOI: 10.1099/mic.0.000372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for assessing temporal variation of growth of fungi on building materials

Abstract: Fungal growth on indoor surfaces can decay building materials and release hazardous substances that affect indoor air quality. Despite the numerous methods available for growth determination, there is no commonly accepted standard. The goal of this study was to compare five different assay methods for the measurement of fungal growth: cultivation, MS-based determination of ergosterol, beta-N-acetylhexosaminidase activity, quantitative PCR and microscopic spore counting. Three fungal species (Aspergillus puulaa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…As such, the assessment and control of microbial contamination in health care facilities is currently a mandatory and vital part of the strategies to prevent and control hospital-acquired infections [7,8]. Aiming at addressing this challenging assessment, several studies have already reported the upmost importance of applying passive sampling methods [9][10][11][12][13]. These methods allow characterization of the contamination from a larger period of time (weeks to several months) [14].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the assessment and control of microbial contamination in health care facilities is currently a mandatory and vital part of the strategies to prevent and control hospital-acquired infections [7,8]. Aiming at addressing this challenging assessment, several studies have already reported the upmost importance of applying passive sampling methods [9][10][11][12][13]. These methods allow characterization of the contamination from a larger period of time (weeks to several months) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Shirakawa et al (2002) noticed fungal growth on the interface between layers of paint and on the interface between paint and substrate. Mensah-Attipoe et al (2016) stress that the fungal grown visible on construction materials is caused by prolonged moisture on their surfaces and that the increase of fungal biomass brings about the difference of antifungal resistance. Johansson, Svensson and Ekstrand-Tobin (2013) concluded that fungal growth is induced when the combination of temperature and humidity exceeds the growth limit curves calculated.…”
Section: IVmentioning
confidence: 99%
“…According to the authors, these results can be explained by two reasons: either the paints had extents of inefficient biocides or the fungi acquired resistance to these agents. Mensah-Attipoe et al (2016) noticed that Aspergillus fungus are more sensitive to variations of humidity than those species of Cladosporium and Penicillium. Still regarding genus Aspergillus, these authors noted that from day 0 to week 1 there was a significant reduction in colony forming units followed by a significant increase until week 4.…”
Section: Morphological Analysismentioning
confidence: 99%
“…However, since early detection of fungal growth is relevant to food safety especially when spoilage fungi produce mycotoxins, the use of more sensitive methods of detection is needed. The measurement of biochemical markers such as ergosterol (Taniwaki et al 2006;Mensah-Attipoe et al 2016) could be an option. However, this is a time consuming and laborious method which lacks of specificity, since it could not distinguish between different fungal species in a mixed culture (Arquiza and Hunter 2014).…”
Section: Introductionmentioning
confidence: 99%